Customer Attitude Towards Loyalty Card of Budget Hotel in Bandung - Hefimaputri, Revi Adelia; Indriani, Mia T. D. (Journal of Business and Management, 2015)
Abstract. The increasing number of hotels in Bandung would lead to the tight competition. To survive the competition, one of the strategies is retaining the customer through loyalty card. However, it is very common to find budget hotel loyalty card which is similar to Luxury hotel. From previous research findings, it is found that offering a single loyalty card to customers that patronize different hotel segments could result in the failure. Therefore, budget hotel need to know what kind of loyalty card is customer really like and prefer that could be measured by calculating customer attitude towards loyalty card of budget hotel. By using Fishbein Multi-attribute Attitude Mode, this research aims to measure and quantify customersâ€™ attitude. Variables of the research are resulted based on combining the result of previous research about hotel loyalty card and customer loyalty. The result of Fishbein Multi-attribute Attitude measurement is + 529.07 or can be translated to positive attitude. Moreover, Above all features, Discount Room Rates has the highest evaluation score which is considered as the most desirable and important to the customer. As recommendation to hotel business, since budget hotel customer are very conscious about price, for further business development, the management should emphasize price and value consideration of its loyalty card features, its benefits, and pricing to make the features attractive.Â Keywords: budget hotel, loyalty card, customer attitude, Fishbein Multi-attribute.